Challenges in talent management in selected public universities - Lukman@Zawawi, Mohamad; Kamal, M.Y. (2017)
Talent Management(TM) has triggered practitioner and academician to dig further in this particular area. In the corporate world, TM has become one of the essential programs that able to value their people. However, TM in public universities in Malaysia is still in early stages whereby there are lots of challenges need to be faced by the management. Therefore, this research conducted to examine the challenges faced by the dean in selected public universities in Malaysia. A qualitative approach has been used towards respondents and information obtained analyzed using ATLAS.Ti. Findings indicated that in TM practices which were attracting, recruiting, developing and retaining talent have their own challenges. Respondents agreed that TM has brought the university to a high level in managing people whereby it helps the employee to feel motivated and appreciated. In conclusion, the introduction of TM in public university in Malaysia has helped the human resource system to be better. The overall concept of TM will enhance employee capabilities and competencies to achieve mission and vision of the organization.